The CXCL12-CXCR4/CXCR7 axis as a mechanism of immune resistance in gastrointestinal malignancies. (October 2020) - Daniel, Sara K.; Seo, Y. David; Pillarisetty, Venu G.
Abstract: Single agent checkpoint inhibitor therapy has not been effective for most gastrointestinal solid tumors, but combination therapy with drugs targeting additional immunosuppressive pathways is being attempted. One such pathway, the CXCL12-CXCR4/CXCR7 chemokine axis, has attracted attention due to its effects on tumor cell survival and metastasis as well as immune cell migration. CXCL12 is a small protein that functions in normal hematopoietic stem cell homing in addition to repair of damaged tissue. Binding of CXCL12 to CXCR4 leads to activation of G protein signaling kinases such as P13K/mTOR and MEK/ERK while binding to CXCR7 leads to β-arrestin mediated signaling. While some gastric and colorectal carcinoma cells have been shown to make CXCL12, the primary source in pancreatic cancer and peritoneal metastases is cancer-associated fibroblasts. Binding of CXCL12 to CXCR4 and CXCR7 on tumor cells leads to anti-apoptotic signaling through Bcl-2 and survivin upregulation, as well as promotion of the epithelial-to-mesechymal transition through the Rho-ROCK pathway and alterations in cell adhesion molecules. High levels of CXCL12 seen in the bone marrow, liver, and spleen could partially explain why these are popular sites of metastases for many tumors. CXCL12 is a chemoattractant for lymphocytes at lower levels, but becomes chemorepellant at higher levels; it is unclear exactly what gradient exists in the tumor microenvironment and how this influences tumor-infiltrating lymphocytes. AMD3100 (Plerixafor or Mozobil) is a small molecule CXCR4 antagonist and is the most frequently used drug targeting the CXCL12-CXCR4/CXCR7 axis in clinical trials for gastrointestinal solid tumors currently. Other small molecules and monoclonal antibodies against CXCR4 are being trialed. Further understanding of the CXCL12- CXCR4/CXCR7 chemokine axis in the tumor microenvironment will allow more effective targeting of this pathway in combination immunotherapy.